Basic and clinical andrology - Société d'andrologie de langue française. (London : BioMed Central, 2013)
"Basic and Clinical Andrology is an open access journal in the domain of andrology covering all aspects of male reproductive and sexual health in both human and animal models. The journal aims to bring to light the various clinical advancements and research developments in andrology from the international community."
Mode of access: World Wide Web.
"Basic and Clinical Andrology is the official journal of French Society of Andrology (SALF)."
Description based on: 23:1 (29 August 2013); title from journal homepage (BioMed Central website, viewed Sept. 9, 2013).
Latest issue consulted: 24:13 (2014) (viewed Sept. 12, 2014).
Keywords: Andrology -- Periodicals; Generative organs, Male -- Diseases -- Periodicals; Infertility, Male -- Periodicals; Andrology; Generative organs, Male -- Diseases; Infertility, Male; Genital Diseases, Male; Genitalia, Male; Infertility, Male; Physiology; Electronic journals